Effect of associated floral diversity on spatial-temporal abundance of aphids and coccinellids in wheat crops - Tulli, Maria Celia (2025)
Wheat crops are affected by aphids (Aphididae) that can be controlled by coccinellids (Coccinellidae). A spatial-temporal dynamics study of aphids and coccinellids in wheat was carried out during the crop cycle at different distances from Associated floral diversity (AFD). Four transects (repetitions) were established and it was fortnightly monitored with sweep net at six distances from AFD (5, 10, 20, 40, 80, and 160 m). Species were identified with a stereoscopic microscope. Aphid distribution pattern differed according to phenological stages: Disperser (tillering and stem elongation), Cultural (booting and anthesis, with maximum densities at 160 m) and Ubiquist (milk and dough grain). Three coccinellids were mostly recorded, Eriopis connexa (Germar), Harmonia axyridis (Pallas) and Cycloneda ancoralis (Germar) which abundance differed according to the site. H. axyridis (76,9 %) prevaled in DFA and E. connexa (71 %) in wheat, with Ecotone and Cultural patterns, respectively. Coccinellid abundance reached its maximum in milk grain with an 82 % reduction of aphid population. The spatial-temporal variability of aphids and coccinellids documented during the crop cycle emphasizes the importance of monitoring areas far from the edge and studying the coccinellid winter ecology for its conservation and its synchronization with aphids.